2019
DOI: 10.1186/s12889-019-7857-z
|View full text |Cite
|
Sign up to set email alerts
|

Projected return on investment of a corporate global health programme

Abstract: BackgroundHealth and wellbeing initiatives vary in effectiveness due to programme design and offerings. The Partnership for Prevention programme expands access to up to 40 evidence-based clinical preventive services for all employees and eligible family members as part of a unique global health initiative.MethodsUsing a published RAND Europe model developed for the company, country-level return on investment was estimated over a five-year timeframe using programme utilisation data. Regional, global, and servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…If the individual participates in preventive programs, the probability of developing diseases or discovering them in advanced stages decreases. Over the past 20 years, several studies [39][40][41][42][43][44][45][46][47] have addressed this issue and there is growing evidence that workplace programs can generate acceptable financial returns for employers investing in them. A study of Johnson and Johnson employees [39] showed a difference in the increase in the average annual costs of internment between workers involved and not involved in lifestyle improvement programs and changes in the workplace, representing $43 and $76, respectively, thus representing a considerable increase in percentage terms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…If the individual participates in preventive programs, the probability of developing diseases or discovering them in advanced stages decreases. Over the past 20 years, several studies [39][40][41][42][43][44][45][46][47] have addressed this issue and there is growing evidence that workplace programs can generate acceptable financial returns for employers investing in them. A study of Johnson and Johnson employees [39] showed a difference in the increase in the average annual costs of internment between workers involved and not involved in lifestyle improvement programs and changes in the workplace, representing $43 and $76, respectively, thus representing a considerable increase in percentage terms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A net saving of $2.18813 (95% CI; $−4.3804; $4.8143) per employee was found as a result of productivity increase. Peik and others [46] applied the Research and Development (RAND) Europe model, a program designed to expand access to up to 40 evidence-based clinical preventive services for all employees and eligible family members, as part of a unique global health initiative at the country level to estimate the return on investment over a five-year timeframe. The study concluded that this program generates a global return of $4.28-$11.88 (after investment cost).…”
Section: Literature Reviewmentioning
confidence: 99%